Food manual grinder / Nur Izzah Putri Shamsul Niza and Ab Aziz Mohd Yusof - Shamsul Niza, Nur Izzah Putri; Mohd Yusof, Ab Aziz (School of Mechanical Engineering, 2023)
Injuries in the kitchen are inevitable during food preparation. A food grinder is a tool used to grind food into a finer form. Cooking accidents often occur when people accidentally cut themselves with sharp blades. To prevent such incidents, an innovative invention has been designed and manufactured to facilitate the cooking process. The main objectives of this project are to design and fabricate a safe and user-friendly manual food grinder. This machine is specifically designed to be easy to use, even for children, and aims to reduce the number of kitchen injuries. The project commenced by conducting surveys and extensive web research to gather relevant information and data. Subsequently, a scaled-down manual-handled food grinder design was developed and fabricated. The food manual grinder is intended for domestic kitchen use, featuring a simple-to-use hand crank mechanism. The grinder is expected to operate smoothly and efficiently, facilitating the grinding of cooking ingredients